Dynamical mechanism of tacit knowledge dissemination based on newman-watts network - Liang, Qianqian; Guo, Lingling; Shen, Jianwei (Frontiers in Physics, 2022)
Exploring the mechanism of tacit knowledge dissemination is the basis of tacit knowledge management. This paper explores the mechanism of tacit knowledge dissemination in Newman-Watts small-world networks using the SIR model. The introduction of diffusion in the traditional diffusion model does not change the stability of the system. Therefore, It cannot explain the dissemination process. We replace the diffusion term with the adjacency matrix of the network to achieve dissemination. The results indicate that the diffusion of tacit knowledge subjects and the entropy of the network (NSE) play a crucial role in generating periodic and local dissemination behaviors. This model can guide significance for effectively accelerating tacit knowledge dissemination and improving the core competitiveness of the enterprise.